Representasi Nilai-Nilai Komitmen Cinta Dalam Film Dua Hati Biru - Fajar Abhirawa; Irwanto; Panji Suratriadi (CV. ITTC INDONESIA, 2025)
Humans are social beings who have a biological need to reproduce through a bond of love commitment, namely marriage. This can be learned through a film that was shown in theaters in 2024, namely entitled Dua Hati Biru, which aims to understand this meaning. The data collection method in compiling the Final Assignment is the method of observation, interviews, and literature studies with the analysis method in the form of qualitative analysis, namely the data analysis method without using statistical analysis. After conducting this research, communication symbols were found according to John Fiske with his semiotic method that about the love commitment presented in the scenes of the Dua Hati Biru film, such as moments when couples understand each other, support and help each other's difficulties. This is an implied meaning that the film wants to convey that when someone commits to love with their partner, actions will appear that support the commitment itself so that communication in the husband and wife relationship runs well